Sosialisasi Prospek Karir pada Bidang Teknologi Informasi di SMKN 1 Purwokerto - Purwono Purwono; Barlian Kristanto; Bala Putra Dewa; Yuris Tri Naili (LPPM Universitas Harapan Bangsa Purwokerto, 2023)
The development of information technology continues to increase lately. Indonesia is one of the countries that is also affected by the development of this information technology. The younger generation is the most important part of a nation that needs to be directed and educated so they can have a better future. The younger generation can take advantage of the potential of technological developments. Emerging various types of new professions in the field of IT makes a promising opportunity. Community service activities carried out by Harapan Bangsa University lecturers and students are a manifestation of the Main Performance Indicators (IKU) of tertiary institutions, namely students who have experience outside the campus and lecturers who are active outside the campus. The activities carried out were socialization related to career prospects in the field of information technology at SMK N 1 Purwokerto which was carried out on February 8 2023. The activities that had been carried out went well and smoothly. This activity has succeeded in opening new insights for students of SMK N 1 Purwokerto about the many career opportunities in the field of information technology. Students can also consider the right major when pursuing higher education if they want a career in information technology